THE EXPRESSION OF RELIGIOUS VIEWS THROUGH LANGUAGE IN CURSES AND BLESSINGS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the linguistic expression of religious views in curses and blessings as culturally marked speech units that reflect the worldview, moral values, and spiritual imagination of a speech community. Curses and blessings are not only emotional reactions or formulaic expressions used in everyday communication; they also function as verbal forms through which people conceptualize divine justice, fate, reward, punishment, protection, and moral responsibility. In philological analysis, such units reveal the close relationship between language, belief, tradition, and collective consciousness. Blessings usually express wishes for divine mercy, prosperity, health, fertility, peace, long life, and spiritual protection, while curses often verbalize the idea of punishment, deprivation, misfortune, or exclusion from sacred favor. The article focuses on how religious concepts are encoded in lexical choices, phraseological structures, metaphorical images, and pragmatic intentions. Special attention is given to the role of sacred names, references to God, destiny, sin, prayer, repentance, and spiritual purity in the formation of these expressions. The study also emphasizes that curses and blessings preserve archaic layers of national mentality and oral tradition, because many of them have been transmitted through family communication, folklore, rituals, and social interaction. From a linguistic point of view, these expressions demonstrate how religious consciousness becomes part of ordinary speech and how language serves as a medium for transmitting cultural memory. The article concludes that the study of curses and blessings is important for understanding the interaction between language and religion, as well as for revealing the semantic, pragmatic, and cultural functions of spiritually motivated verbal formulas.